Pathological Internet Use and Psychosocial Risk Factors among ASEAN University Students - Turnbull, Niruwan; Peltzer, Karl; Pengpid, Supa; Low, Wah Yun; Huu, Thang Nguyen; Rochmawati, Erna; Win, Hla Hla (Mazandaran University of Medical Sciences, 2018)
Background: Pathological internet use may lead to serious psychosocial problems and dysfunction. Objectives: The purpose of the study was to investigate the prevalence of pathological internet use among undergraduate university students in five ASEAN countries in relation to sociodemographics, internet use variables, psychosocial factors, and comorbid symptoms. Methods: In a cross-sectional survey in 2015 in Indonesia (Yogyakarta), Malaysia (Kuala Lumpur), Myanmar (Yangon), Thailand (MahaSarakham), and Vietnam (Hanoi), 3240 undergraduate university students (Mean age = 20.5 years, SD = 1.6), who were randomly selected, responded to a questionnaire including the "Young Diagnostic Questionnaire for Internet Addiction" (YDQ) and other measures. Results: Overall, the prevalences of pathological internet use were 35.9% (ranging from 16.1% in Myanmar to 52.4% in Thailand), maladaptive use 34.8% and adjusted Internet users 29.9%. In multivariate logistic regression analysis, internet use variables (heavy overall Internet use, heavy Internet use for recreational purposes, and heavy smartphone use), psychosocial factors (the experience of childhood physical abuse, childhood sexual abuse, lack of social support, and poor academic performance), and comorbid symptoms (having a self-classified gambling problem, hazardous or harmful alcohol use, past 12-month drug use, severe depression, sleeping problems, having attempted a suicide, and PTSD symptoms) were found to be associated with pathological internet use. Conclusions: The study found a very high prevalence of pathological internet use; those students lacking psychosocial support and having comorbid symptoms were at the highest risk.